1996
DOI: 10.1111/j.1365-2516.1996.tb00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and IgG subclass analysis of antibodies to factor VIII in multitransfused haemophiliacs and healthy individuals

Abstract: Using a binding assay to immobilized factor VIII (F VIII) (ELISA) we measured the amount of IgG with binding capacity to FVIII, in the plasma of patients with an inhibitor to F VIII, in multitransfused haemophiliacs without inhibitor and in a control group of blood donors. It was shown that the amount of IgG bound to VIII was elevated in patients with an inhibitor although a weak correlation could be established between the inhibitor titre (BU) and the amount of bound IgG. In all haemophiliacs without inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…It is generally agreed that IgG4 is the predominant anti ‐ FVIII antibody immunoglobulin subclass, often occurring with at least one other heavy chain subclass, usually IgG1 [1,10,24–26]. Similarly, in our study we found that IgG was the predominant immunoglobulin class in both acquired and congenital haemophilia A, but three patients with acquired haemophilia A also had antiFVIII IgM antibodies.…”
Section: Discussionsupporting
confidence: 84%
“…It is generally agreed that IgG4 is the predominant anti ‐ FVIII antibody immunoglobulin subclass, often occurring with at least one other heavy chain subclass, usually IgG1 [1,10,24–26]. Similarly, in our study we found that IgG was the predominant immunoglobulin class in both acquired and congenital haemophilia A, but three patients with acquired haemophilia A also had antiFVIII IgM antibodies.…”
Section: Discussionsupporting
confidence: 84%
“…We and others have demonstrated, at the clonal level, a restricted specificity of B cell clones isolated from hemophilia A patients with inhibitor [19,20,21]. It also suggests that the inhibitory antibodies measured by Bethesda assay belong to the IgG isotype, a finding already reported by other investigators [13,22,23,24,25]. We have also demonstrated elevated levels of IgA in a small number of inhibitor-positive patients.…”
Section: Discussionsupporting
confidence: 69%
“…None of our samples was found to be of the IgG1 or IgG3 isotype. Predominance of IgG4 has been reported by almost all investigators [23,24,25, 27]. Conflicting results, however, have been observed for other IgG subclasses.…”
Section: Discussionmentioning
confidence: 47%
“…Several studies have shown anti-FVIII IgG 4 to be the best immunologic indicator of the presence of a functional inhibitor to FVIII. [8][9][10][11] In addition, we examined the stability of rFVIII under the various PHT conditions tested.…”
mentioning
confidence: 99%